School Well-Being Boosts Student Motivation in Indonesia: Kesejahteraan Sekolah Meningkatkan Motivasi Belajar Siswa di Indonesia - Priambadi, Braniodi Shandy; Nastiti, Dwi (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the relationship between school well-being and learning motivation among Islamic Vocational High School students in Tulangan, Sidoarjo. Using a quantitative correlational method, 222 students were selected from a population of 497 through stratified random sampling. Validated scales measured school well-being and learning motivation, with data analyzed using Pearson product-moment correlation via JASP software. Results showed a significant positive correlation (r=0.432, p<0.001), indicating that higher school well-being is associated with increased learning motivation. These findings suggest that improving school infrastructure and resources can enhance student motivation, highlighting the need for collaborative efforts to boost educational quality. Highlight: Positive correlation between school well-being and learning motivation identified. Enhanced infrastructure boosts student motivation. Collaboration with parents and institutions crucial for educational quality. Keyword: School well-being, learning motivation, Islamic vocational students, quantitative study, Pearson correlation